A narrowband ultrasonic ranging method for multiple moving sensor nodes - Ashhar, Karalikkadan (2021)
Accurate ranging using narrow-band ultrasonic transducers in small-scale environments can be used for indoor localization, human motion capture, and robotic navigation. One of the main problems faced by the ultrasonic localization systems is the ranging error due to the Doppler shift. Existing methods for Doppler correction employ a bank of matched filters at the receiver end which is computationally intense and complex. On the other hand, enabling multiple access for the ultrasonic localization systems is a challenging task due to multiple access interference. We propose a method to measure the range between multiple ultrasonic mobile nodes and static anchors in which we track the Doppler velocity and correct the errors between the transmitted and the received signals due to the Doppler effect. We utilize range-Doppler coupling to estimate the Doppler shift and adjust the range values calculated by correlation. In our method, a unique set of two chirp signals are used for each transmitter to get one sample reading. The simulation results show high ranging accuracy and robustness using the proposed method as the Doppler velocity increases. A pendulum experiment was conducted to validate the method using narrowband ultrasonic sensors. The multiple access interference problem was tackled by orthogonal coding, the chirp signals and Doppler correction. An improvement in the ranging accuracy was observed over traditional methods using chirp signals without Doppler correction.